Who are the students enrolled in a federal public university? (Research, Society and Development, 2022)
Mapping the profile of students entering public universities is already an objective of several studies, but this profile has been increasingly unique. Thus, we seek in this study to raise indicators that help us in understanding the reality and particularities of students of different higher education courses of a federal public university in southeastern Pará, through the socioeconomic diagnosis of these students. In this article, a structured questionnaire with direct questions is used, calculating a stratified sample per course and class/semester, considering the level of significance equal to 5%, based on the number of students enrolled in the 2nd semester of 2019, which totaled a sample of 251 students. Among the main results, the predominance of female students, who declared themselves brown, without disabilities, who live with their parents in their own homes, depend on public transportation, no employment relationship, do not receive any social program benefit from the federal government and do not participate in extracurricular activities. Thus, some characteristics prevailing in the academic environment are understood and that influence the performance and stability of students at the university, thus it becomes more feasible to develop policies of permanence and that favor the learning of these students in higher education.